A Comparative Study of Power Semiconductor Devices for Industrial PWM Inverters - Gianluca Sena; Roberto Marani; Gennaro Gelao; Anna Gina Perri (International Journal of Power Electronics and Drive Systems (IJPEDS), 2016)
The growing demand of energy translates into efficiency requirements of energy conversion systems and electric drives. Both these systems are based on Pulse Width Modulation (PWM) Inverter. In this paper we firstly present the state of art of the main types of semiconductors devices for Industrial PWM Inverter. In particular we examine the last generations of Silicon Carbide (SiC) MOSFETs and Insulated Gate Bipolar Transistors (IGBTs) and we present a comparison between these devices, obtained by SPICE simulations, both for static characteristics at different temperatures and for dynamic ones at different gate resistance, in order to identify the one which makes the PWM inverter more efficient.